2022
DOI: 10.1016/j.xphs.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microparticle Based Formulation for Topical Delivery of FOL-005, a Small Peptide

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These observations provide evidence for a pro-angiogenic effect of FOL-026. Earlier experimental and clinical studies have shown that treatment with the FOL-026 analogue FOL-005 as well as osteopontin 4,18 stimulates hair growth but the mechanisms responsible for this effect have been unclear. Yano and coworkers 9 were first to demonstrate that the transition of resting hair follicles into the anagen growth phase is preceded by an increased perifollicular vascularization and that this is activated by an increased expression of VEGF in follicular keratinocytes in the outer root sheath of the hair follicle and FOL-005 has been shown to also accumulate around and affect these cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations provide evidence for a pro-angiogenic effect of FOL-026. Earlier experimental and clinical studies have shown that treatment with the FOL-026 analogue FOL-005 as well as osteopontin 4,18 stimulates hair growth but the mechanisms responsible for this effect have been unclear. Yano and coworkers 9 were first to demonstrate that the transition of resting hair follicles into the anagen growth phase is preceded by an increased perifollicular vascularization and that this is activated by an increased expression of VEGF in follicular keratinocytes in the outer root sheath of the hair follicle and FOL-005 has been shown to also accumulate around and affect these cells.…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs on 6-well plates were starved for 24 hours or for siRNA transfection for 48 hours and dissociated by TrypLE Express (Gibco, Grand Island, NY) to obtain cell suspensions. Cells were seeded at a density of 1.5 x 10 4 / well in 96-well plate pre-coated with Geltrex reduced growth factor basement membrane matrix (Gibco, Grand Island, NY) in Medium 200 complete culture medium containing different concentration of FOL-026 peptide. After 12-18 hours of incubation, random images were recorded by an inverted microscope (Nikon, Eclipse TE2000-U, Kawasaki, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations